“Building block picture” of the electronic structure of aqueous cysteine derived from resonant inelastic soft X-ray scattering - Meyer, Frank; Blum, M.; Benkert, A.; Hauschild, D.; Nagarajan, S.; Wilks, R. G.; Andersson, J.; Yang, W.; Zharnikov, Michael; Bär, M.; Heske, C.; Reinert, F.; et al. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2014)
The electronic structure of the amino acid l-cysteine in an aqueous environment was studied using resonant inelastic soft X-ray scattering (RIXS) in a 2D map representation and analyzed in the framework of a “building block” approach. The element selectivity of RIXS allows a local investigation of the electronic structure of the three functional groups of cysteine, namely, the carboxyl, amino, and thiol groups, by measuring at the O K, N K, and S L2,3 edges, respectively. Variation of the pH value allows an investigation of molecules with protonated and deprotonated functional groups, which can then be compared with simple reference molecules that represent the isolated functional groups. We find that such building blocks can provide an excellent description of X-ray emission spectroscopy (XES) and RIXS spectra, but only if all nearest-neighbor atoms are included. This finding is analogous to the building block principle commonly used in X-ray absorption spectroscopy. The building blocks show a distinct spectral character (fingerprint) and allow a comprehensive interpretation of the cysteine spectra. This simple approach opens the path to investigate the electronic structure of more complex biological molecules in aqueous solutions using XES and RIXS.